2019
DOI: 10.1111/his.13895
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation that somatic mutations of beta‐2 microglobulin correlate with a lack of recurrence in a subset of stage II mismatch repair deficient colorectal cancers from the QUASAR trial

Abstract: Aims Beta2‐microglobulin (B2M) forms part of the HLA class I complex and plays a role in metastatic biology. B2M mutations occur frequently in mismatch repair‐deficient colorectal cancer (dMMR CRC), with limited data suggesting they may protect against recurrence. Our experimental study tested this hypothesis by investigating B2M mutation status and B2M protein expression and recurrence in patients in the stage II QUASAR clinical trial. Methods and results Sanger sequencing was performed for the three coding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…B2M mutations have been reported to be associated with prolonged survival for non-metastatic MSI cancer patients ( 8 , 10 , 15 , 16 ). To the best of our knowledge, no systematic data exist about the survival of B2M -mutant stage IV MSI cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B2M mutations have been reported to be associated with prolonged survival for non-metastatic MSI cancer patients ( 8 , 10 , 15 , 16 ). To the best of our knowledge, no systematic data exist about the survival of B2M -mutant stage IV MSI cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…What may be the mechanisms responsible for a favorable clinical course of B2M -mutant cancers in the absence of ICB? Previous studies have demonstrated that B2M loss limits the metastatic potential in MSI colorectal cancer ( 8 , 15 , 16 ) and other tumor types, such as uveal melanoma ( 18 ). Although the details are not yet fully understood, one hypothesis suggests that the lack of HLA class I antigens as ligands to the NK cell-inhibitory receptors renders B2M -mutant cells susceptible to NK cell-mediated elimination ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…25 Non-silent mutations in β2M have been reported in a broad range of patients 26 and LOH at chromosome 15q21, assessed using two microsatellite markers, was found in 44% of bladder carcinomas (n=69), 35% of colon carcinomas (n=95), 16% of melanomas (n=70) but only 7% of renal cancers (n=45). [27][28][29] Interestingly the rate of mutations was appreciably higher in microsatellite unstable disease (particularly colorectal, gastric and uterine cancers) and was associated with an increased overall burden of mutations for both microsatellite stable and unstable disease, commensurate with the role of the HLA system in presenting acquired mutations for immunosurveillance. Moreover, loss of B2M mediated acquired resistance to immune checkpoint inhibitors (ICIs) has been reported in clinical investigations.…”
Section: Mutations In B2mmentioning
confidence: 99%
“…In this regard, Kloor et al evaluated B2M mutation status in 104 dMMR/MSI CRC patients and found B2M mutation was only detected in localized disease [ 95 ]. Barrow et al investigated B2M mutation and protein expression in 229 stage II colon cancer patients (121 dMMR/MSI cases) in the QUASAR study [ 96 ]. The investigators detected B2M mutations in 32% (39/121 cases) of dMMR/MSI tumors and none of these patients had tumor recurrence while 18% of B2M wild-type tumors developed disease recurrence.…”
Section: Novel Biomarkers In Dmmr/msi Crcsmentioning
confidence: 99%